2017
DOI: 10.1002/job.2170
|View full text |Cite
|
Sign up to set email alerts
|

The psychological microfoundations of corporate social responsibility: A person‐centric systematic review

Abstract: This article aims to consolidate the psychological microfoundations of corporate social responsibility (CSR) by taking stock and evaluating the recent surge of person-focused CSR research. With a systematic review, the authors identify, synthesize, and organize three streams of micro-CSR studies-focused on (i) individual drivers of CSR engagement, (ii) individual processes of CSR evaluations, and (iii) individual reactions to CSR initiatives-into a coherent behavioral framework. This review highlights signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
817
0
26

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 549 publications
(869 citation statements)
references
References 127 publications
(212 reference statements)
26
817
0
26
Order By: Relevance
“…Although CSR has emerged as a prominent concept in business practice and in the strategy field (Porter and Kramer, 2011), its conceptualization at the individual of analysis has remained limited until a recent period (Aguinis and Glavas, 2012;Gond et al, 2017). In particular, relatively little is known about how individuals manage CSR within organizations, as prior research has focused on quantitative analyses of how employees perceive CSR and react to their perceptions of CSR (e.g., El-Akremi et al, forthcoming), and have neglected to analyze how and why CSR becomes meaningful for different individuals (Aguinis and Glavas, forthcoming).…”
Section: Consolidating the Constructivist Micro-foundations Of Csrmentioning
confidence: 99%
“…Although CSR has emerged as a prominent concept in business practice and in the strategy field (Porter and Kramer, 2011), its conceptualization at the individual of analysis has remained limited until a recent period (Aguinis and Glavas, 2012;Gond et al, 2017). In particular, relatively little is known about how individuals manage CSR within organizations, as prior research has focused on quantitative analyses of how employees perceive CSR and react to their perceptions of CSR (e.g., El-Akremi et al, forthcoming), and have neglected to analyze how and why CSR becomes meaningful for different individuals (Aguinis and Glavas, forthcoming).…”
Section: Consolidating the Constructivist Micro-foundations Of Csrmentioning
confidence: 99%
“…Our model also has implications for CSR research at the micro-level (Gond, El Akremi, Swaen, & Babu, 2017;Risi & Wickert, 2017). In an experiment whose subjects were business and economics students, Hafenbrädl and Waeger (2016) found that studying business and economics-rather than other disciplines-increases the belief in a positive CSP-CFP link, and that 80 percent of their subjects believed in that link.…”
Section: /53mentioning
confidence: 99%
“…But this knowledge gap is now being filled by what can be appropriately described as an explosion of micro-CSR research conducted at the individual-level of analysis focusing on how and why job seekers, employees, and other individuals perceive and react to CSR (Glavas, 2016a). This explosion of scholarly activity is reflected in the recent publication of several reviews of micro-CSR research on employee recruitment, and reactions to CSR among incumbent employees (Peloza and Shang, 2011; Aguinis and Glavas, 2012; Jones and Willness, 2013; Willness and Jones, 2013; Rupp and Mallory, 2015; Glavas, 2016b; Gond et al, 2017; Jones and Rupp, in press). The micro-CSR literature also appears to be undergoing rapid maturation, as evidenced by advances in measurement (El Akremi et al, 2015), and the development of overarching theories about how and why individuals react to CSR practices, including theory about employee motives (Rupp et al, 2006; Bauman and Skitka, 2012; Glavas, 2016b; Jones and Rupp, in press), the underlying mechanisms through which job seekers are attracted by CSR (Jones et al, 2014), and a needs-based model of CSR motives that applies to micro-, meso-, and macro-level stakeholders (Aguilera et al, 2007).…”
Section: Introductionmentioning
confidence: 99%